Tubercular myositis of infraspinatus: a rare clinical entity - Verma, Vikas; Yadav, Yogesh Kumar; Rastogi, Anuj; Mohammed, Farid (International Journal of Research in Medical Sciences, 2017)
Tuberculosis of the musculoskeletal system is generally confined to bones and joints. The surrounding soft tissue is secondarily infected. Tuberculous bursitis, tenosynovitis and primary pyomyositis are rarer manifestations of the disease. Of these, primary tuberculouspyomyositis is probably the rarest entity. We report a case of tubercular myositis of infraspinatus in an 8 year-old female who presented with pain, low grade fever, weight loss, anorexia, progressively increasing pain in the scapular region and restriction of movements. There was no history of trauma, diabetes, immunosuppression, corticosteroid usage, or renal failure. History of contact was present. Tenderness was present along the medial border of scapula and movements of upper extremity requiring movement of the scapula were painful and grossly restricted. MRI of the scapulothoracic region and shoulder revealed small amount of fluid along medial border of scapula with T2 hyperintensity of infraspinatus. Histopathology showed caseous necrosis, inflammatory cells and granulomatous cells suggestive of tuberculosis. Polymerase Chain Reaction for Mycobacterium tuberculosis was found to be positive. Patient was started on four-drug antitubercular treatment and regular dressings. The patient’s general condition improved and at 4 weeks post starting ATT, there was no pain and the patient was able to perform complete range of movement. This is probably the first reported case of tubercular myositis of infraspinatus in an immunocompetent patient without any identifiable focus elsewhere in the body. Rarity of the condition, presence of characteristic findings on MRI and histopathology make the case illustrative for young Orthopaedics surgeons.